Ultraviolet radiation promotes the production of hispidin polyphenols by medicinal mushroom Inonotus obliquus. Issue 11 (November 2022) - Zhou, Rong; Yang, Hanbing; Lu, Ting; Zhao, Yanxia; Zheng, Weifa
Abstract: Production of hispidin polyphenols in Inonotus obliquus is a stress-induced response triggered by environmental factors. As one of the important environmental factors, ultraviolet (UV) radiation plays regulatory roles in fungal growth and development. However, whether UV radiation regulates the formation of hispidin polyphenols remains to be established. In this study, we cultivated I. obliquus on solid medium and imposed intermittent UV radiation. We showed that UV exposure inhibited the growth of mycelia but increased the production of polyphenols. Further bioassays revealed that UV radiation also increased the catalytic activities of phenylalanine ammonia-lyase (PAL) and chalcone isomerase (CHI), up-regulated expression of genes related to redox, transcriptional regulation, and metabolism. In addition, the total extracts from the UV-irradiated group were more capable of scavenging DPPH and ABTS + free radicals, especially at the later stage of culture. Thus, UV radiation, acting as one of the environmental factors, stimulated the accumulation of polyphenols in I. obliquus by regulating the activities of enzymes and the expression of genes related to growth and metabolism, and can be tentatively used as a feasible strategy to enhance the production of polyphenols in I. obliquus . Highlights: Ultraviolet radiation significantly increased the accumulation of polyphenols in I. obliquus. Ultraviolet radiation promoted the activities of PAL and CHI related to polyphenol synthesis. Ultraviolet radiation enhanced the antioxidant activity of polyphenols.